The cooling effect of green spaces as a contribution to the mitigation of urban heat: a case study in Lisbon - Oliveira, Sandra (2011)
Green areas in the urban environment can contribute to the mitigation of the Urban Heat Island. In a context of climate change, with the expected increase in temperature, dryness and intensity of heat waves, green areas assume even higher importance as they can create a cooling effect that extends to the surrounding areas. This study analyses the thermal performance of a small green space (0.24 ha) and its influence in the surrounding atmospheric environment of a densely urbanised area in Lisbon. Measurements of weather parameters (temperature, relative humidity, wind speed, solar and infrared radiation) were carried out along a selected path, starting from inside the green area to surrounding streets with different orientations and solar exposure. It was found that the garden was cooler than the surrounding areas, either in the sun or in the shade. These differences were higher in hotter days and particularly related to the mean radiant temperature (Tmrt). The highest difference found was of 6.9 °C in relation to air temperature and 39.2 °C in relation to Tmrt; in both cases this difference occurred between the shaded site inside the garden and the sunny site in an E–W oriented street in the southern part of the studied area. Besides the local weather conditions, particularly the low wind speed, the sun exposure and the urban geometry are the potential factors that explain these differences. The cooling effect of green areas on the surrounding environment can be enhanced by additional measures related to the urban features of each city.